Shared Genetic Predisposition in Peripartum and Dilated Cardiomyopathies. Issue 3 (September 2016) - Ware, J.S.; Li, J.; Mazaika, E.; Yasso, C.M.; DeSouza, T.; Cappola, T.P.; Tsai, E.J.; Hilfiker-Kleiner, D.; Kamiya, C.A.; Mazzarotto, F.; Cook, S.A.; Halder, I.; et al.
Abstract : ( N Engl J Med . 2016;374:233–241) It is possible that peripartum cardiomyopathy is influenced by genetic factors, though this remains unclear. Similar to idiopathic dilated cardiomyopathy, this disease is associated with decreased systolic function, enlarged cardiac dimensions, and nonspecific histologic findings. These similarities are significant in that idiopathic dilated cardiomyopathy has been shown to be caused by a number of gene mutations. The authors of this study sequenced the DNA of 172 women suffering from peripartum cardiomyopathy to investigate whether there was a contribution from variants in the 43 genes known to be associated with dilated cardiomyopathy.